Breeding Potential for Increasing Carbon Sequestration via Rhizomatous Grain Sorghum - Yaojie Zheng; Dirk B. Hays; Russell W. Jessup; Bo Zhang (Plants)
Rhizomes, key carbon sequestration sinks in perennial crops, are hypothesized to exhibit a trade-off with grain yield. This study evaluated rhizomatous grain sorghum populations for increasing carbon sequestration potential. Twelve F3:4 heterogeneous inbred families (HIFs) from a Sorghum bicolor (L.) Moench × Sorghum propinquum (Kunth) Hitchc cross were tested in a greenhouse, and two F4:5 HIF progenies were field tested. Traits measured included rhizome biomass, root biomass, total belowground biomass, and grain yield. Rhizome biomass showed high heritability (0.723) and correlated strongly with belowground biomass (r1 = 0.95; r2 = 0.97) in both F4:5 HIFs, suggesting the potential of rhizomes to sequester carbon. Contrary to the hypothesized trade-off, a positive relationship between rhizome biomass and grain yield was observed, potentially via rhizome-derived shoots, and individual plants pyramiding high rhizome biomass, biomass yield, and grain yield were also identified. Using bulked segregant analysis (BSA), twenty simple sequence repeat (SSR) markers linked to eight genomic regions associated with rhizome presence were identified, with five regions potentially being novel. This study suggests that breeding rhizomatous grain sorghum with high rhizome biomass could enhance carbon sequestration while preserving agronomic yields, offering new insights for future breeding and mapping initiatives.